Answer: B
m<G<m<x
Step-by-step explanation:
Just did it
Answer:
Step-by-step explanation:
Since you have
+
5
y
in one equation and
−
5
y
in the other equation, you can add both equations to cancel out the y terms and solve for x.
−
6
x
+
5
x
=
−
x
5
y
−
5
y
=
0
1
+
10
=
11
therefore
−
x
=
11
multiplying both sides by -1:
x
=
−
11
plugging this back into the first equation:
−
6
(
−
11
)
+
5
y
=
1
66
+
5
y
=
1
subtracting 66 from both sides:
5
y
=
−
65
divide both sides by 5:
y
=
−
13
putting the x-values and y-values into one point gives:
(
−
11
,
−
13
)
as the solution
Height is 18 for question 3.
Answer:
Step-by-step explanation:
4.5C